Operative treatment of cervical spine tumors - Baranowska, Alicja; Lisiecki, Janusz; Magura-Witkowski, Maciej; Baranowski, Paweł; Kłosiński, Piotr; Kruk, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2003)
This publication presents an analysis of methods and results of the surgical treatment of patients with cervical spine tumors. The study included 30 patients suffering from cervical spine tumors treated in our departments in a 4-year period, from September 1998 to September 2002 and consisted of 18 women and 12 men aged between 35 and 75. Except for 3 chordomas and 2 giant-cell tumors, 3 myelomas and 1 hemangioma, all the others were metastatic tumors originating mainly from the breast and prostatic cancer. In 6 causes the origin of the tumor has not been established. Nerve root pain syndromes, restricted mobility of the neck and neurological defects were the main reason for guiding the diagnostics, assessing the stage of the disease and making a decision on the operative treatment. During the operation the anterior approach was used in 25 cases, posterior approach in 3 cases and 2 patients were operated using both approaches. Autogenous graft from the iliac bone fixed with titanium implants was used for the stabilization. Surgical complications and the worsening of the neurological condition were not observed after the operative treatment. Pain control, regaining the neurological function and stability of the cervical spine were assessed. In all cases reduction of the pain was achieved, which significantly improved the comfort of life. The neurological improvement was observed in most cases. Subjective and objective improvement for the patients was observed after the surgical treatment and FPI cases made the histopathological diagnosis possible which provided the basis for the guided treatment.